Serotonin selectively attenuates glutamate-evoked activation of noradrenergic locus coeruleus neurons - Aston-Jones, G (J Neurosci, 1991)
The effect of 5-HT on activity of noradrenergic locus coeruleus (LC) neurons was studied using microiontophoretic and micropressure drug application in anesthetized rats. 5-HT had no consistent effect on LC spontaneous discharge, eliciting a modest decrease overall. However, 5- HT reliably attenuated responses of LC neurons to excitatory amino acids (EAAs), one of the major classes of transmitters in afferents to these neurons. This effect was specific for EAA responses because it occurred for glutamate and kainate but not for ACh. In contrast, iontophoretic norepinephrine (NE) selectively attenuated spontaneous activity but not responses evoked by either glutamate or ACh. The responsiveness of LC neurons to EAAs as quantified by a response- contrast measure (evoked excitation/basal activity) was markedly reduced by 5-HT, but was increased by NE. For ACh, such responsiveness of LC cells was not changed by 5-HT, but was increased by NE. The effects of 5-HT were prevented and reversed by iontophoretically applied antagonists of 5-HT receptors, methysergide and methiothepin. Thus, 5-HT appears to selectively interact with EAA responses of LC neurons, acting as a filter to attenuate LC activity linked to its major EAA inputs while allowing other channels afferent to the LC (e.g., those utilizing ACh) to be expressed.